Characterisation of umbilical cord blood derived haematopoietic stem and progenitor cells from HIV exposed infants that are HIV negative at birth - Pepper, Michael Sean (University of Pretoria, 2024)
Thesis (PhD (Medical Immunology))--University of Pretoria, 2024.